The Valuation of Sustainable Entrepreneurship - Gloria Chrisanskia Sibarani; Radityo Fajar Arianto (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2022)
In the recent years, sustainability has been a new way of living which people have started to gain knowledge and implement the lifestyle itself. This study intended to measure the gap of the relationship of undergraduate students’ valuation towards sustainability, their frequency of social media exposure, and their motivation towards entrepreneurship towards their valuation of sustainability in entrepreneurship. A total of 208 valid respondents contributed in this research with the implementation of a quantitative research. The results shows that the valuation of sustainability, social media exposure frequency, and drives for entrepreneurship does have an effect towards students’ valuation of sustainability in entrepreneurship. The result from this research could be useful for future studies and education regarding sustainability to furthermore improve students’ knowledge and awareness of sustainability and entrepreneurship alongside their exposure of social media. Future research should explore more possible factors that influence sustainability in entrepreneurship and reach a more diverse scope of sample.